Curcumin decreases astrocytic reaction after gliotoxic injury in the rat brainstem - Eduardo Bondan; Carolina Cardoso; Maria de Fátima Martins (Arquivos de Neuro-Psiquiatria)
ABSTRACT Recent studies have demonstrated that curcumin (Cur) has antioxidant, anti-inflammatory and anti-fibrotic effects. Ethidium bromide (EB) injections into the central nervous system (CNS) are known to induce local oligodendroglial and astrocytic loss, resulting in primary demyelination and neuroinflammation. Peripheral astrogliosis is seen around the injury site with increased immunoreactivity to glial fibrillary acidic protein (GFAP). This investigation aimed to evaluate the effect of Cur administration on astrocytic response following gliotoxic injury. Wistar rats were injected with EB into the cisterna pontis and treated, or not, with Cur (100 mg/kg/day, intraperitoneal route) during the experimental period. Brainstem sections were collected at 15, 21 and 31 days after EB injection and processed for GFAP immunohistochemical staining. Astrocytic reactivity was measured in a computerized system for image analysis. In Cur-treated rats, the GFAP-stained area around the lesion was significantly smaller in all periods after EB injection compared to untreated animals, showing that Cur reduces glial scar development following injury.